Murder in Lascaux - Draine, Betsy, 1945- (Terrace Books/University of Wisconsin Press, 2011)
The cave of Lascaux may be closed to the public, but five scholars a day are allowed inside, and Nora Barnes has finagled an appointment. True, she may have fudged a bit in her letter to the authorities, but she does teach art history, and she isn't about to miss her chance to see the world's most famous prehistoric paintings. Nora and her high-spirited husband, Toby, are visiting the Dordogne, in the southern French region of the Aquitaine. Aware that the Dordogne's renown for cave art is matched only by its reputation for delicious cuisine, the couple has also signed up for a cooking class at a nearby château, but they soon find that more than food is on their minds.